2019
DOI: 10.1111/age.12762
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐genome sequencing reveals a large deletion in the MITF gene in horses with white spotted coat colour and increased risk of deafness

Abstract: White spotting phenotypes in horses are highly valued in some breeds. They are quite variable and may range from the common white markings up to completely white horses. EDNRB, KIT, MITF, PAX3 and TRPM1 represent known candidate genes for white spotting phenotypes in horses. For the present study, we investigated an American Paint Horse family segregating a phenotype involving white spotting and blue eyes. Six of eight horses with the white-spotting phenotype were deaf. We obtained whole-genome sequence data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…Visual inspection of the registration photographs for these 97 horses revealed that 31 possessed patterns consistent with white-spotting loci. These 31 included many phenotypes resembling those generated by alleles known but not genotyped in this cohort, including MITF*SW4 (Hauswirth et al 2013a), MITF*SW5 (Henkel et al 2019) and more than 27 other alleles at the KIT locus. We also observed among these 31 horses some well-recognized patterns with as yet unknown genetic etiology (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Visual inspection of the registration photographs for these 97 horses revealed that 31 possessed patterns consistent with white-spotting loci. These 31 included many phenotypes resembling those generated by alleles known but not genotyped in this cohort, including MITF*SW4 (Hauswirth et al 2013a), MITF*SW5 (Henkel et al 2019) and more than 27 other alleles at the KIT locus. We also observed among these 31 horses some well-recognized patterns with as yet unknown genetic etiology (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Of these known alleles, nine are common to and routinely tested for in the APHA population (Table 1). Others, like MITF-Splash White 4 and many of the KIT*W series alleles (at least 30 variants recorded in OMIA), are breed specific and not present in the Paint Horse, whereas some like MITF-Splash White 5 were not yet commercially available for testing at the time the study began and therefore were not examined (Hauswirth et al 2013b;Henkel et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…WGS has recently identified a genetic cause of occipitoatlantoaxial malformation (OAAM) in an Arabian horse (Bordbari et al 2017) and dwarfism in a Miniature Shetland pony (Metzger et al 2017). WGS data have also been used to identify novel pigmentation variants (Henkel et al 2019). Finally, WGS has been used to investigate characteristics of highly selected breeds (Metzger et al.…”
Section: Genomics Tools and Resourcesmentioning
confidence: 99%
“…Visual inspection of the registration photographs for these 98 horses revealed that 31 possessed patterns consistent with white spotting loci. These 31 included many phenotypes resembling those generated by alleles known but not genotyped in this cohort, including SW4 , SW5 (Henkel et al, 2019), and more than 27 other alleles at the KIT locus. We also observed among these 31 horses some well-recognized patterns with yet unknown genetic etiology (i.e.…”
Section: Photographic Estimation Of Spotting Patterns Miscategorizes mentioning
confidence: 99%